SKEMA AKTAN DAN STRUKTUR FUNGSIONAL DALAM NOVEL SA'ATU AL-BAGHDAD KARYA SHAHAD AL-RAWI (KAJIAN SEMIOTIKA NARATIF A. J. GREIMAS) - Alissa Fariztina; Mawardi Mawardi; Irfan Addriadi (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
War and collective trauma often appear in modern Arabic literature, especially in works that reflect the socio-political conditions in the Arab world. Shahad al-Rawi's novel Sa'atu al-Baghdad depicts childhood experiences in Baghdad during war, embargo, and destruction. The narrative of this novel is not only built from the story, but also from the structure and complex relationships between characters. This study aims to analyze the narrative structure of the novel using A. J. Greimas' narrative semiotics approach, especially the actant scheme and functional structure. The method used is qualitative-descriptive with reading and note-taking techniques. The results of the study show that the main character acts as a subject who is driven by past memories to find the meaning of life. The relationship between actants such as family, friends, and lovers acts as supporters, while war and trauma act as opponents that strengthen the dynamics of the story. The functional structure describes the psychological transformation of the main character from an initial peaceful situation, experiencing an existential crisis, to achieving inner stability. Greimas' narrative semiotic theory successfully reveals the depth of the story structure and meaning of this novel. This study contributes to the narrative analysis of modern Arabic novels by applying Greimas' semiotic model, which has never been used before in this literary text.